Rapid and on-site electrochemical detection of bisphenol A and arsenic in drinking water using a novel electrode array - Uludag, Yildiz; Olcer, Zehra; Dogan, Canan; Muhammad, Turghun; Altintas, Zeynep (Tubitak Scientific & Technological Research Council Turkey, 2019)
The paper describes a novel dip-and-gauge hand-held sensor device for the rapid, cost-effective, and on-site detection of bisphenol A and arsenic in drinking water samples. Different working electrode diameters ranging from 1.5 mm to 4 mm were designed and fabricated to construct a new electrochemical biosensor. The sensor was employed for the chronoamperometric detection of bisphenol A and voltammetric determination of arsenic in drinking water samples. Bisphenol A measurements resulted in a detection limit of 10 ng mL(-1) with a linear range of 0-4000 ng mL(-1). Baby products and bottles have to be completely free of bisphenol and hence a liquid-phase microextraction method has been developed to reduce the detection limit further to 0.6 ng mL(-1). Arsenic detection was investigated in the concentration range of 0.4-250 ng mL(-1) with a detection limit of 1.9 ng mL(-1). The current study showed that the designed electrode array allows low detection limits (below threshold levels), although a bare gold surface is used for the study. Hence, together with a hand-held sensor device that works by simply dipping the sensor chip into a water container, this cost effective system has the potential to be used either by household consumers or for on-site inspection purposes.
Keywords: Electrode array; bisphenol; arsenic; amperometry; voltammetry; hand-held sensor